HYBRID LI-FI AND WI-FI SECURE TRANSMISSION MODEL FOR SMART COMMUNICATION SYSTEMS. - Kaur, Charanjit; Dubey, Mithilesh Kumar; Dubey, Sudha (Scientific Culture, 2026)
The rapid growth of global internet users, surpassing 6 billion in 2025, alongside advancements in mobile and Wi-Fi connectivity, has underscored the need for innovative wireless communication technologies.This study investigates how Li-Fi and Wi-Fi can be combined in a hybrid network architecture, utilizing Wi-Fi's extensive infrastructure and Li-Fi's built-in security and high-speed capabilities.The proposed HCK algorithm enhances this hybrid system by implementing robust security measures, including RSA, AES, and ChaCha20 encryption, alongside authentication and non-repudiation protocols. Simulation results demonstrate the HCK algorithm's superior performance, achieving a throughput of 988.56, speed of 1468.68, bandwidth of 398.46, and a low packet drop rate of 0.018%, significantly outperforming existing algorithms. The hybrid network ensures scalability, energy efficiency, and security, addressing critical gaps in current systems, particularly for IoT applications. By combining Li-Fi's secure, interference-free transmission with Wi-Fi's mobility, this framework offers a scalable and reliable solution for modern connectivity demands